Levantamentos altimétricos realizados por meio aerofotogramétrico: um estudo multicaso - Silva, Leonardo de Araújo (Universidade Federal Rural do Semi-Árido, 2019)
The innovation in photogrammetric aerial mapping has been growing exponentially in recent years, because Unmanned Aerial Vehicles (UAVs) provide an efficiency in the preparation of studies and projects, thus providing less time to obtain data, such as reducing execution costs . Several products can be obtained in the field of engineering with the use of this technology, either in the topographic field, as a planialtimetric survey, in the obtaining of information of the terrestrial surface, and also in altimetric projects, in obtaining relief of the terrain. Based on this, the objective was to compare the results obtained by altimetric surveys carried out by aerophotogrammetric method, by means of variation of overlap and use of adjustments through point of controls. For these surveys, steps were taken for the workflow: choice of study area, flight planning for aerophotogrammetric data collection, data collection and images for processing and obtaining the final products that is necessary for comparative analysis and effects. From the generation of reports provided by the software, the results obtained between the three surveys were compared. The objective of the study is directed to the calculation of the volumetry, it was noticed that the overlap influences significantly in the results without control points to correct the coordinates in the calculation of the volume, so for the flight without use of control points indicates the lateral and longitudinal overlap of 65% and 85%, respectively. However the control points are necessary for a good final quality of the products generated.
Altimetric surveys performed by aerophotogrammetric: a multi-case study
Monografia
Keywords: Mapeamento aéreo; Topografia; Relevo do terreno; Cartografia digital; Aerolevantamento; Aerial mapping; Topography; Terrain relief; Digital cartography; Aerial surveying; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA